Pengaruh Radiasi Sinar Gamma dan Asam Fusarat untuk Meningkatkan Ketahanan Abaka (Musa textilis Nee) terhadap Fasariurn oxysporum - Damayanti, Fitri; Suharsono, Suharsono; Mariska, Ika (JURNAL BIOLOGI INDONESIA, 2002)
ABSTRACTEffect of gamma radiation and fusaric acid for resistance to wild Fusarium disease onabaca plant (Mum textillis Nee). The problem in abaca production is wilt disease infectioncaused by Fusarium oxysporzim. The resistant variety against the pathogen has not beenavailable yet. The disease resistance character of the species might be improved throughsomaclonal variation and in vitro selection. Different pure toxin of fusaric acid concentration(0, 15,30,45,60, and 75 mg/l) was used as component selection to get new hope numbers ofresistant abaca to wilt Fusarium disease through in vitro selection. Concentration of 45 mgllfusaric acid is lethal for abaca, so we used this concentration as dose of selection to selectshoots from irradiated calli. Gamma irradiation was used as mutagent to increase somaclonalvariation on abaca. Six levels of gamma-ray radiation (0, 0.5, 1, 2, and 3 Krad) were appliedto embriogenic calli. Increasing dose of radiation decreased the viability of calli. LDso wasfound between 1-1.5 Krad of radiation dose. In vitro selection was carried out in two stages.The concentration of selection of hsaric acid in stage I1 was increased one level to theconcentration in stage 1. Stage I selection of shoots from irradiated calli on mediumcontaining pure toxin 45 mg/l fusaric acid, showed that the survival capacity decreasing withthe increasing doses of gamma irradiation. In stage 11, shoots from irradiated calli (at 0.5 and1 Krad) could survive on medium containing 60 mg/l fusaric acid. In medium selectioncontaining 50% filtrate F. oxysporum, fusaric acid resistant shoots were also filtrate resistant.There was a correlation between in vitro fusaric acid and filtrate of F. oxysporum resistantplant and conidia suspension of F. oxysporum resistkt plant in the greenhouse.Keywords: Gamma radiation, in vitro selection, fusaric acid, Musa textilis, Fusariumoxysporum